Rates of escalation to triple COPD therapy among incident users of LAMA and LAMA/LABA. (June 2018) - Hahn, Beth; Hull, Michael; Blauer-Peterson, Cori; Buikema, Ami R.; Ray, Riju; Stanford, Richard H.
Abstract: Background: Improved outcomes have been reported for patients with chronic obstructive pulmonary disease (COPD) receiving combination long-acting muscarinic antagonist/long-acting β2 -agonist (LAMA/LABA) therapy compared with LAMA monotherapy. However, little is known about the relative characteristics of these patients and their rates of escalation to triple therapy (TT, combining a LAMA, LABA, and inhaled corticosteroid). This study aimed to characterize patients initiating treatment with the LAMA tiotropium (TIO) and the fixed-dose LAMA/LABA combination therapy umeclidinium/vilanterol (UMEC/VI), and to compare rates of escalation to TT between patients receiving these therapies. Methods: Retrospective study of patients with COPD enrolled in a US health insurance plan during 2013–2015 and newly initiated on TIO or UMEC/VI. Patients were ≥40 years of age at index (date of therapy initiation) with continuous enrollment for 12 months pre-index and ≥30 days post-index. LAMA users were propensity score matched 1:1 to LAMA/LABA users, with TT initiation rates reported by cohort using pharmacy claims. Results: 35, 357 patients initiating on TIO and 2407 patients initiating on UMEC/VI were identified. After propensity score matching, the rate of TT initiation was significantly higher in new TIO users (n = 1320) than in new UMEC/VI users (n = 1320) (0.92 vs 0.49 per 100 months of exposure, respectively; p < 0.001). Relative to the UMEC/VI cohort, the TIO cohort had an 87% higher risk of TT initiation (hazard ratio: 1.87; 95% confidence interval: 1.4–2.5; p = 0.001). Conclusions: Patients receiving UMEC/VI progressed to TT more slowly, and were at lower risk of progressing to TT, than patients receiving TIO. Highlights: UMEC/VI therapy was associated with slower progression to triple therapy than TIO. The risk of triple therapy initiation was 87% higher in TIO users than UMEC/VI users. Results suggest better symptom control and slower disease progression with UMEC/VI.